Utilization of Low-Grade Ceiba Pentandra Oil for Biodiesel Production Using Nano Zinc Oxide Catalyst Supported by Fly-Ash Waste - Somawiharja, Yohannes -; Siswoyo, Deddy Kurniawan Putra; Asri, Nyoman Puspa (Jurnal IPTEK, 2024)
Biodiesel is a renewable energy and potentially to be developed to replace fuel derived from fossil oil. This study explores the oil of Ceiba pentandra (OCP), a low-quality oil with high free fatty acids as a feedstock for biodiesel production.  A cost-effective nano-doped zinc oxide heterogeneous catalyst was developed using fly ash waste as a support called NZO/FA. The catalyst was synthesized using co-precipitation, precipitation, and impregnation methods. Biodiesel is made through a transesterification process using a laboratory-scale glass-type batch reactor. The experiment examines how the varied temperature (60-80°C with an interval of 10°C) and varied reaction time (3-5 hours with an interval of 0.5 h) influence biodiesel yield, heating value, and final product properties. Meanwhile, other conditions were fixed at a molar ratio of oil/methanol of 1:15 and a catalyst dosage of 5%. The results showed the highest yield of 98.69%, and a GHV of 37.95 MJ/kg was obtained at a reaction temperature of 80°C and a reaction time of 5 hours. Meanwhile, almost all of the characteristics of the biodiesel produced meet SNI 7182:2015.